Fish oil quality of by-product (fish skin) from swangi fish - La Ode Huli; Sugeng Heri Suseno; Joko - Santoso (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2014)
The skin of swangi fish is a potential fish skin to be produced for fish oil. The objectives of this research were aimed to determine the yield and the best quality of fish oil and also to compare fatty acid profile of the fish according to different extraction methods. Fish oil extractions were used by wet rendering method with extraction temperatures of 60, 70, 80, 90, 100°C for 20, 30, and 40 minutes. Fish oil quality was determined by the chemical oil characteristics i.e. PV, FFA, AV, anisidin, and TOTOX. Fatty acid profile was analyzed using gas chromatography (Shimadzu). The results of the study showed that the highest fish oil yield in each treatment was obtained extraction temperature of 60°C for 30 minutes with percentage of 0.33, (70°C for 30 minutes) 0.46, (80°C for 30 minutes) 1.23, (90°C for 20 minutes) 1.14 and (100°C for 20 minutes) 0.84. These values were lower compare to Bligh & Dyer and Soxhlet methods. Then, the best fish oil quality was resulted on temperature extraction of 60°C for 30 minutes with PV, FFA, anisidin, AV, and TOTOX were 9.17 meq/kg, 6.92%, 13,77 mg KOH/g, 0.86 meq/kg and 19.19 meq/kg, respectively. FUFA fatty acid compositions of swangi skin fish oil especially EPA and DHA in wet rendering method were gained 0.73% and 2.53%, respectively. These results were lower than Bligh & Dyer method which was consisted of 3.66% (EPA), and 13.29% (DHA) and also Soxhlet extraction method with value of EPA was 2.78% and DHA was 9.62%.Keywords: EPA, extraction temperature, DHA, fish oil quality, fish skin